484 Solriamfetol Titration & AdministRaTion (START): Physician titration strategies in a hypothetical patient with narcolepsy. (3rd May 2021) - Singh, Haramandeep; Hyman, Danielle; Parks, Gregory; Chen, Abby; Baldys, Beth; Ito, Diane; Thorpy, Michael
Abstract: Introduction: Solriamfetol (Sunosi®), a dopamine/norepinephrine reuptake inhibitor, is approved (US and EU) to treat excessive daytime sleepiness (EDS) in adults with narcolepsy (75–150 mg/day) or obstructive sleep apnea (OSA) (37.5–150 mg/day). Patient characteristics, comorbidities, and other EDS medications can influence treatment strategies. To understand factors physicians consider when initiating solriamfetol, this study analyzed titration strategies for a hypothetical patient. Methods: This virtual, descriptive, cross-sectional, qualitative survey enrolled US-based physicians treating patients with EDS due to OSA and/or narcolepsy. Responses to 4 open-ended questions regarding a hypothetical patient were recorded. Patient scenario: 32-year-old woman with narcolepsy (Epworth Sleepiness Scale score=8) using an amphetamine stimulant (35 mg/day) and sodium oxybate (6 g/night) for 6 months and occasionally experiencing non-use-limiting but bothersome adverse events (AEs) with the stimulant. Content analysis of the recordings identified themes in the responses; a trained linguist captured language choices/patterns. Results: Twenty-six physicians (neurologists, n=7 [27%]; internists/family practitioners, n=7 [27%]; pulmonologists, n=6 [23%]; psychiatrists, n=5 [19%]; otolaryngologists, n=1 [4%]) representing 781 patients on stable solriamfetol doses participated; 19 (73%) were board-certified in sleep disorders. Physicians had been treating narcolepsy a mean 15.7±6.6 years. Most (21 [81%]) thought the patient appropriate for solriamfetol, 3 (12%) thought not appropriate, and 2 (8%) thought appropriateness depended on other factors. Sixteen physicians (62%) suggested adjusting her stimulant, 3 (12%) the stimulant and sodium oxybate, and 1 (4%) neither. Nineteen (73%) would titrate solriamfetol per the label, with 13 (50%) aiming for 75 mg/day and 8 (31%) for 150 mg/day. Physicians emphasized stopping the stimulant before starting solriamfetol: 10 (39%) would taper down before starting solriamfetol, 7 (27%) while starting solriamfetol, and 1 (4%) while aiming to eventually switch; 8 (31%) would discontinue abruptly. Nineteen physicians (73%) would not change their approach if the stimulant dose were 60 mg/day. Most clinicians would change their approach if AEs occurred while starting solriamfetol by taking a slower or more gradual approach, while some would titrate off the stimulant more aggressively. Conclusion: Physicians considered existing medications and potential AEs in their titration strategy when initiating solriamfetol. Support (if any): Jazz Pharmaceuticals